Training a polyfunctional teacher within the dialogue of culture and sport in modern learning community - Munirova, Leila; Gvozdeva, Anita (Видавництво Львівської політехніки, 2013)
The realization of a multifunctional approach in the system of professional physical teacher training necessitates the inclusion in educational programmes of different profiles the development of individual trajectories. In order to form professional competencies in modern learning community it is necessary to implement educational programmes in a number of different academic activities for student choice. Training a polyfunctional teacher in the dialogue of culture and sport provides didactic models and key typology of such competences , cross-cultural management associated with building a learning society, learning cities of culture and sport.
Keywords: learning community; training a polyfunctional teacher; a multifunctional approach; comparative didactics; professional competences; international culture and sport; social mobility; dialogue of cultures in sport education; UNESCO programmes